Green Investment Practices and Challenges in Indonesia's Investment Legal System - Ayuningtias, Farah Tarisya (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
Green investment is a vital instrument in achieving sustainable development amidst the global climate crisis. As a country committed to green development agendas, Indonesia has shown increasing interest in environmentally friendly investments, particularly in sectors such as renewable energy, reforestation, and carbon trading. However, the current investment law system in Indonesia remains inadequately equipped to address the complexities of this green transformation. This article examines the current practices of green investment in Indonesia and analyzes its legal challenges using a socio-legal approach. Regulations such as Law No. 25 of 2007 on Investment, the Omnibus Law on Job Creation, and various environmental laws still lack legal clarity on the definition of “green investment,” fiscal and legal incentives, and institutional coordination. In comparison, countries like Singapore and the European Union have adopted sustainable finance frameworks with clear taxonomies and strict oversight mechanisms to prevent greenwashing. The findings of this study highlight that the success of green investment initiatives in Indonesia relies heavily on reforming its investment legal system to be more responsive to environmental concerns and sustainability goals. Policy harmonization between investment, environmental, and fiscal regulations is urgently needed to strengthen systematic and equitable green investment governance in Indonesia